Digital native media in the Andean community: a view from their characteristics - Gonzales Córdova, Mayra Paola (European Public & Social Innovation Review, 2024)
The advent of the Internet 30 years ago, has prompted the media to face new challenges and as a result we can observe a series of significant changes and a new way of conceiving the media that are on the web. Media and journalists have understood that the new ways to reach audiences are in digital environments. The objective of this study on digital native media in the Andean Community (CAN) is to analyze the characteristics according to their typology. The research is developed based on a mixed methodology that includes a literature review, the recording of a database for subsequent analysis and observation. The research design follows a descriptive, explanatory and exploratory model; initially, it seeks to identify the CAN cybermedia through variables that allow obtaining details of each of them. Subsequently, information is gathered on their evolution and characteristics. In conclusion, this study has shown that, the countries of the CAN, the development of online media, known as cybermedia, share several characteristics influenced mainly by economic, political and social factors, as well as by technological adoption despite the existing digital divide. From the data collected, Ecuador, Peru, Colombia and Bolivia register for this study a total of 74 digital native cybermedia.